Clinical characteristics leading to misdiagnosis of abdominal tuberculosis in children: a systematic review and meta-analysis - Siddiqui, Mohd Jaish; Karmacharya, Abhishek; Wan, Xuemeng; Zhu, Yu; Wan, Chaomin; Luo, Shuanghong (Frontiers in Pediatrics, 2025)
IntroductionAbdominal tuberculosis (ATB) in children is an uncommon form of extrapulmonary tuberculosis that often presents with non-specific symptoms. These features frequently overlap with other abdominal conditions, increasing the risk of misdiagnosis or delay in diagnosis. Although individual case series have reported such diagnostic challenges, a pooled analysis of clinical characteristics associated with misdiagnosis has not been previously conducted. This study aimed to identify the clinical characteristics that contribute to the misdiagnosis of ATB in children through a systematic review and meta-analysis.MethodsWe conducted a systematic review and meta-analysis following PRISMA 2020 guidelines. A comprehensive literature search was carried out using PubMed, Web of Science, and Google Scholar for studies published between 1900 and 2024. Eligible studies were pediatric case series that included confirmed ATB cases and provided information on initial misdiagnosis or diagnostic delays. Patients who were misdiagnosed or delayed in diagnosis were categorized under the “misdiagnosed” group. Data were extracted on presenting clinical features, and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using Review Manager (RevMan 5.4). Heterogeneity was assessed using the I2 statistic, and publication bias was evaluated using funnel plots.ResultSeven studies met the inclusion criteria, comprising a total of 60 pediatric ATB cases. Among them, 24 were classified as misdiagnosed and 36 were diagnosed without delay. No clinical characteristics were statistically significantly associated with misdiagnosis. Although ascites and abdominal distension were more frequently observed in misdiagnosed cases, overall heterogeneity was low across most outcomes.ConclusionsClinical characteristics alone are not reliable indicators for diagnosing ATB. Ascites and abdominal distension may increase the risk of misdiagnosis, underscoring the importance of early suspicion and timely diagnostic evaluation in TB-endemic regions.